A Comparative Study of Pressure Losses and Hole Cleaning Efficiency of Water and Polymer solutions in Horizontal Wells - Ahmed Mohammed, Karrar; A. Al-Haleem, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The main objective of this study is to experimentally investigate the effect of the CMC polymeric drag reducer on the pressure drop occurred along the annulus of the wellbore in drilling operation and investigate the optimum polymer concentration that give the minimum pressure drop. A flow loop was designed for this purpose consist from 14 m long with transparent test section and differential pressure transmitter that allows to sense and measure the pressure losses along the test section. The results from the experimental work show that increasing in polymer concentration help to reduce the pressure drop in annulus and the optimum polymer concentration with the maximum drag reducing is 0.8 kg/m3. Also increasing in flow rate and corresponding fluid velocity in the gap of the annulus helped to reduce the pressure losses due to fluid flow.